Analisis Indeks Pencemaran di Sungai Akibat Kegiatan Industri Sabun Detergen di Wilayah Surabaya - Rizka Novembrianto; Muhammad Aditya Muzaky (Prosiding ESEC, 2023)
The current decline in river water quality is inversely proportional to the increase and development of industrial activities which generate not only waste from the industrial process itself but also from domestic waste in the industry as well as household activities along the river flow, this can become a serious problem for existing biota and living creatures. The pollution that occurs can be measured from the pollution index to determine the level of pollution for several parameters such as BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), TSS (Total Suspended Solid), pH, and Amonia. The purpose of this study is to identify the pollution index that occurs. The results of this study show that rivers in the city of Surabaya have a moderate level of pollution. This is based on the results of calculating the pollution index with high BOD and Amonia values from the detergent soap industry.